Mental Health Literacy Reduces Mental Disorder Stigma in Society - S, Rizky Hadi Rahmani; Fahmawati, Zaki Nur; Affandi, Ghozali Rusyid (Indonesian Journal of Cultural and Community Development, 2025)
The general background mental health issues remain a major global health challenge, including in Indonesia, where mental illness is often stigmatized. Specific background mental illness stigma is prevalent in society, manifesting in negative attitudes towards individuals with mental disorders, thus affecting their acceptance and treatment. Knowledge gap there is limited research exploring the relationship between mental health literacy and mental illness stigma within community settings in Indonesia. This study aims to investigate the correlation between mental health literacy and mental disorder stigma among residents of a selected community. Results the findings reveal a significant negative correlation between mental health literacy and mental disorder stigma, indicating that higher levels of mental health literacy are associated with lower levels of stigma. Novelty this study contributes to the limited body of knowledge by demonstrating that improving mental health literacy can effectively reduce mental disorder stigma in community settings. Implications these results suggest that public health interventions focusing on mental health education may help reduce stigmatization, fostering a more supportive environment for individuals with mental health disorders, which may ultimately lead to better access to mental health services and outcomes. Highlights: Higher mental health literacy lowers mental disorder stigma. Stigma reduction improves mental health support in communities. Public health education can reduce mental disorder misconceptions. Keywords: Mental Health, Mental Disorder, Stigma, Community Attitudes, Education